2009
DOI: 10.1103/physrevb.80.024113
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of stress in individual grains and twins in a magnesium alloy aggregate

Abstract: This is an in situ measurement of the full stress tensor and its evolution in a growing deformation twin and, simultaneously, in the grain where the twin forms. The combined information provides a detailed picture of the grain-twin interaction. The three-dimensional x-ray diffraction method using 80.7 keV synchrotron x rays allows us to in situ investigate a grain within the bulk of a magnesium alloy ͑AZ31͒ sample that is compressed to activate the ͕1012͖͗1011͘ tensile twin system. We observe that the stress s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
87
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(96 citation statements)
references
References 17 publications
9
87
0
Order By: Relevance
“…Such an approach, however, does not take into account the complexity of the local stress state inside or in the vicinity of the primary twin (Aydiner et al 2009) or the mechanisms required for nucleating the secondary twin. As a consequence, the results have proved inconsistent with experimental observations.…”
Section: *Author For Correspondence (Irene@lanlgov)mentioning
confidence: 99%
“…Such an approach, however, does not take into account the complexity of the local stress state inside or in the vicinity of the primary twin (Aydiner et al 2009) or the mechanisms required for nucleating the secondary twin. As a consequence, the results have proved inconsistent with experimental observations.…”
Section: *Author For Correspondence (Irene@lanlgov)mentioning
confidence: 99%
“…Aydiner et al [93] used three-dimensional high-energy XRD to study the stress states within the twin and parent grains of a large grain Mg alloy in compression, where the {1012} tensile twin was activated. Resolution of the stress state of twin and parent revealed significantly different shear stresses, attributed to the constraint of the twin domain inhibiting deformation and leading to an increased back stress in the parent grain.…”
Section: (B) Twinning Deformation Studiesmentioning
confidence: 99%
“…Related arguments, based on self-strain accommodation have been proposed to account for the variant selection during double twinning in Mg-alloys [1,14,25]. Based on in-situ 3D-XRD observations Aydiner et al have reported that the stress state within a twin can be significantly different from that in the untwinned matrix [19]. For the grain tracked by Aydiner et al the stresses within each twin variant were observed to increase with increasing strain, though the stress values within each variant were different and differed to the applied macroscopic stress.…”
Section: Dependence On the Local Stress Conditionsmentioning
confidence: 99%
“…Although it is possible to determine the true twin shape within each grain using either serial sectioning [18] or a 3D-XRD approach [19], both of these methods are time consuming and require complicated apparatus. In order therefore to estimate the twin extent (variant volume fraction) within each grain some assumptions were made concerning the 3-dimensional geometry of the twin to allow the use of standard stereological methods [20].…”
Section: Twin Volume Fractionmentioning
confidence: 99%